Ginsenoside Rb1 induces hepatic stellate cell ferroptosis to alleviate liver fibrosis via the BECN1/SLC7A11 axis - Lifan Lin; Xinmiao Li; Yifei Li; Zhichao Lang; Yeping Li; Jianjian Zheng (Elsevier, 2024)
Liver fibrosis is primarily driven by the activation of hepatic stellate cells (HSCs), a process associated with ferroptosis. Ginsenoside Rb1 (GRb1), a major active component extracted from Panax ginseng, inhibits HSC activation. However, the potential role of GRb1 in mediating HSC ferroptosis remains unclear. This study examined the effect of GRb1 on liver fibrosis both in vivo and in vitro, using CCl4-induced liver fibrosis mouse model and primary HSCs, LX-2 cells. The findings revealed that GRb1 effectively inactivated HSCs in vitro, reducing alpha-smooth muscle actin (α-SMA) and type I collagen (Col1A1) levels. Moreover, GRb1 significantly alleviated CCl4-induced liver fibrosis in vivo. From a mechanistic standpoint, the ferroptosis pathway appeared to be central to the antifibrotic effects of GRb1. Specifically, GRb1 promoted HSC ferroptosis both in vivo and in vitro, characterized by increased glutathione depletion, malondialdehyde production, iron overload, and accumulation of reactive oxygen species (ROS). Intriguingly, GRb1 increased Beclin 1 (BECN1) levels and decreased the System Xc-key subunit SLC7A11. Further experiments showed that BECN1 silencing inhibited GRb1-induced effects on HSC ferroptosis and mitigated the reduction of SLC7A11 caused by GRb1. Moreover, BECN1 could directly interact with SLC7A11, initiating HSC ferroptosis. In conclusion, the suppression of BECN1 counteracted the effects of GRb1 on HSC inactivation both in vivo and in vitro. Overall, this study highlights the novel role of GRb1 in inducing HSC ferroptosis and promoting HSC inactivation, at least partly through its modulation of BECN1 and SLC7A11.